Strategies of the Regional Leaders of Muhammadiyah Bojonegoro in Against the Radicalism Movement - Tohari, Chamim (LPPM IAIN Kudus, 2022)
This study examines the contribution of the Regional Leaders of Muhammadiyah Bojonegoro in an effort to stem the outbreak of the radicalism movement. The problem is limited to the following: (1) What are the views (regarding the definition, characteristics, and statements of agreeing or disagreeing) of Muhammadiyah leaders in Bojonegoro towards the Islamic radicalism movement? (2) What efforts can be taken by Muhammadiyah in Bojonegoro in stemming the spread of Islamic radicalism in society, especially in Bojonegoro? (3) In the field of da’wah, what strategies are used to minimize the possibility of spreading Islamic radicalism in society? The results of this study are: First, regarding the definition of radicalism according to figures and leaders of Muhammadiyah Bojonegoro, it is understood as a movement that wants to completely change the social order in unconstitutional ways. Among Muhammadiyah figures in Bojonegoro considers that radicalism is a product of conspiracy, so that in this context the meaning of radicalism is biased. However, all Bojonegoro Muhammadiyah leaders agreed that Muhammadiyah refused and would fight radicalism. Second, among the efforts/contributions of the Bojonegoro Muhammadiyah Regional Leaders in overcoming radicalism are manifested in various work programs such as implementing the policies of the Muhammadiyah Central Leadership to enlighten the community by showing the face of Islam that is rahmatan li al-‘alamin. Third, Muhammadiyah Bojonegoro does not use a special strategy either in the field of da’wah and in other fields related to combating radicalism, because in general the Muhammadiyah movement from the central level to the lowest level is a movement that shows the spirit of wasathiyah/moderate, inclusive, and promotes tolerance. But the most tangible contribution made by Muhammadiyah Bojonegoro is to instill moderate religious understanding in the community in a structured and systematic manner. The contribution of this research is to provide solutions for the government and society in general on how to spread the spirit of religious moderation structured and systematic.